NAVIGATING NETWORKED TIME: VISUAL SELF-IDENTITY CONSTRUCTION AND MANAGEMENT AMONG YOUTH - Gorea, Michelle (AoIR Selected Papers of Internet Research, 2018)
According to dominant theorizations of contemporary society, many people’s daily practices now occur within, and reproduce, a social world where media are the fundamental reference and resource for the development of the self (Couldry and Hepp 2017:15). Although previous research has revealed the mutual shaping of technologies, interaction, and identity in the broader contexts of economic and social change related to ‘millennials’, we know little about the precise ways in which these practices occur and how the self is being differently constructed over time. Using a multi-method qualitative approach, this work in progress paper explores three key questions: 1) What happens when visuality becomes a part of youth’s everyday practices of interaction? 2) What roles are images playing in routine interaction among youth? 3) How and in what ways does the maintenance of a visually ‘mediated presence’ in social media shape youths’ views of the self? This paper elaborates on findings within three categories that illustrate youth’s visual practices and how they are differently understood over time: (1) images of the self in the moment; (2) images of the self over time; and (3) images of the self under surveillance. The preliminary findings of this research suggest that although youth’s technological practices may not all be new, there are significant aspects of visuality that alters some of the key factors shaping young people’s use and understandings of new media technologies.